SISTEM INFORMASI INVENTORY BERBASIS WEB MENGGUNAKAN METODE OOAD PADA PT BGA - Deddy, Deddy; Arnomo, Sasa Ani (Computer Based Information System Journal, 2024)
Rapid developments in the field of communications have sparked public interest in switching to information and communication technology. The use of information technology by companies plays an important role in simplifying and speeding up their business management. PT Bestbuild Globalindo Aluminum is a company engaged in manufacturing aluminum frames, doors and windows. As the company develops and the number of inventory items increases, problems arise that require attention, namely the difficulty in obtaining fast, precise and accurate information regarding existing inventory items. From these problems, it is necessary to design and build a more structured and efficient goods inventory information system. The aim of this research is to design and build an inventory information system that is expected to increase the efficiency of inventory management, and provide more accurate and reliable information. The research method used by researchers is OOAD (Object Oriented Analysis Design) with modeling using UML. This inventory information system was designed and built using the PHP programming language and data storage via a MySQL database. The inventory information system that has been built can provide up-to-date reports to company leaders regarding inventory items at PT Bestbuild Globalindo Aluminum.